Assessment for health equity of PM2.5 exposure in bikeshare systems: The case of Divvy in Chicago. (September 2019) - Qian, Xiaodong; Wu, Yizheng
Abstract: Introduction: Bikeshare is becoming more and more popular around the world. Many cities in the United States have implemented their own bikeshare systems or are considering having one. Among many other benefits by bikeshare, physical health improvement has been mentioned as one of them as a common sense. However, not enough attention has been paid to potential health impacts when using bikeshare. This is not even to mention how the health impact is distributed among different groups. To address this research gap, we conducted a preliminary study to analyze the uneven distribution of health impacts by making bikeshare trips. Method: In our research, we chose the Divvy bikeshare system in Chicago since it is currently one of the biggest systems in the USA and its trip data are open. By incorporating emission and air dispersion modeling tools, we first estimated the high-resolution air pollution concentration level in the city. Then, we quantified the trip-based PM2.5 exposure by including every trip route and duration time. Finally, we conducted a spatial analysis for health exposure related to bikeshare trips in disadvantaged areas. Results: In Chicago, most of routes with high PM2.5 exposure index are distributed in the southwest of Chicago, where there are more minority populations or low-income communities. From the station level, most of the stations in disadvantaged areas have a high level of PM2.5 exposure index on average. Conclusions: Our research has clearly shown that users from disadvantaged areas are more likely to take a risk of absorbing more PM2.5, especially when traveling to other areas with more job opportunities and other essential services by bikeshare. In summary, our research points out an ignored aspect in planning bikeshare. Bicycle infrastructure design and air pollution control should be integrated into the process of bikeshare promotion in disadvantaged areas. Highlights: Equity study related to health impacts by shared mobility. The trip-based health exposure by including every trip route and air concentration. Evaluation of health impact of bikeshare for different race/ethnicity and income groups.